Heparinase I treatment to overcome RNA quantification interference in heparinized liver donor samples: One size fits all? - Mar Dalmau; Ramón Charco; Itxarone Bilbao; Cristina Dopazo; Mireia Caralt; José Andrés Molino; Concepción Gómez-Gavara (PLoS ONE, 2025)
Background MicroRNAs have emerged as potential biomarkers of liver injury during organ transplantation due to their specificity, easy detection and stability in many biofluids. Heparin, which has a well-known inhibitory effect on RT-qPCR based measurements, is commonly used during organ donation. Heparinase I treatment has been used to overcome the inhibiting effect of heparin in RNA RT-qPCR analysis. However, there is a lack of evidence regarding its effective, feasible use improving specific miRNA quantification yield in the liver transplant setting. The aim of this study is to evaluate the effect of heparinase I on miRNA detection levels by RT-qPCR in different samples from liver donors. Methods Prospective, single-centre study including evaluation of liver biopsy, perfusate fluid and serum from deceased organ donors from October 2019 to May 2021. Samples from brain death donors (DBD, n = 4) and donors after circulatory death recovered with abdominal normothermic regional perfusion (DCD n = 4) were analysed for the presence of liver-injury related miRNAs (miR-122 and miR-148a) in the absence or presence of heparinase I (6 IU or 12 IU) to evaluate its effect on miRNA detection levels by RT-qPCR. A subgroup of heparinized serum samples from patients undergoing cardiopulmonary bypass was analysed for validation purposes. The study is registered with ClinicalTrials.gov (NCT06611046), and accrual is complete. Results The expression of miR-122 relative to reference genes was 44.5, 16.8 and 4.2-fold higher in liver biopsy, perfusates and serum respectively, while miR-148a was 3.4, 2.2 and 2.6-fold higher, without differential expression between donor groups (p > 0.05). Heparinase I treatment did not improve PCR results and affected miRNA detection yields in a dose-dependent way with delayed and dispersed Ct values. In highly heparinized DCD serum samples, heparinase I treatment significantly reduced the relative expression of miR-122 and miR-148a compared to non-treated samples, 2-fold and 6.1-fold, p < 0.05 respectively. Moreover, treatment with heparinase I led to a rise in lost values, from 12.5% to 25% in perfusates and 67.7% to 68.7% in serum samples treated with 6IU and 12IU of heparinase I respectively. Conclusions The need for heparinase I treatment to overcome RNA quantification interference in heparinized samples should be addressed in each individual analysis. Heparin inhibition seems variable among miRNAs, and the additional handling with heparinase may affect reliable miRNA quantification due to RNA degradation, introducing bias in gene expression interpretation.